Altered thyroid hormone levels affect the capacity for temperature-induced developmental plasticity in larvae of Rana temporaria and Xenopus laevis. (May 2020) - Ruthsatz, Katharina; Dausmann, Kathrin H.; Drees, Claudia; Becker, Laura I.; Hartmann, Lisa; Reese, Janica; Reinhardt, Steffen; Robinson, Tom; Sabatino, Nikita M.; Peck, Myron A.; Glos, Julian
Abstract: Anuran larvae show phenotypic plasticity in age and size at metamorphosis as a response to temperature variation. The capacity for temperature-induced developmental plasticity is determined by the thermal adaptation of a population. Multiple factors such as physiological responses to changing environmental conditions, however, might influence this capacity as well. In anuran larvae, thyroid hormone (TH) levels control growth and developmental rate and changes in TH status are a well-known stress response to sub-optimal environmental conditions. We investigated how chemically altered TH levels affect the capacity to exhibit temperature-induced developmental plasticity in larvae of the African clawed frog ( Xenopus laevis ) and the common frog ( Rana temporaria ). In both species, TH level influenced growth and developmental rate and modified the capacity for temperature-induced developmental plasticity. High TH levels reduced thermal sensitivity of metamorphic traits up to 57% ( R. temporaria ) and 36% ( X. laevis ). Rates of growth and development were more plastic in response to temperature in X. laevis (+30%) than in R. temporaria (+6%). Plasticity in rates of growth and development is beneficial to larvae in heterogeneous habitats as it allows a more rapid transition into the juvenile stage where rates of mortality are lower. Therefore, environmental stressors that increase endogenous TH levels and reduce temperature-dependent plasticity may increase risks and the vulnerability of anuran larvae. As TH status also influences metabolism, future studies should investigate whether reductions in physiological plasticity also increases the vulnerability of tadpoles to global change. Highlights: A capacity for developmental plasticity makes anuran larvae less vulnerable to climate change. Environmental stressors lead to high levels of TH via the activation of stress-hormones. High thyroid hormone levels reduce the capacity for temperature-induced plasticity. Warm adapted species show a reduced capacity for developmental plasticity. Larvae may suffer from an interactive effect of stressors caused by global change.